163k views
2 votes
Evaluate the expression.

-5 x -0.2 (-0.5 - negative one)
Write your answer as an integer or a decimal. Do not round.
V

User Charli
by
4.9k points

2 Answers

4 votes

Answer: 0.5

Explanation:

-5*(-0.2(-0.5-(-1)))=

1*(-0.5+1)=

-0.5+1=0.5

User Andrew Corsini
by
4.5k points
0 votes

Answer:

0.5.

Explanation:

1. Write the expression.


-5*-0.2 (-0.5 - (-1))=

2. Simplify the parenthesis.


-5*-0.2 (-0.5+1)=\\\\-5*-0.2 (0.5)

3. Multiply.


-5*-(0.1)=\\ \\0.5

User BabaVarma
by
4.8k points